Aspecte psihopedagogice și metodologice de educație multilingvă a elevilor de liceu din perspectiva motivațională [Articol] - Wittman, Hana (Print-Caro, 2023)
The concept of "curriculum" known in professional language as curriculum is a concept from the field of education that is used to describe an outline or a folder of general instructions that deal with the form and manner of teaching and the assessment of knowledge and skills in any particular profession or field of study. When I come to investigate the differences between bilingual students learning a foreign language, and monolingual students learning a foreign language, of course, the examination of the teaching plans is also necessary and requires a systematic and in-depth approach. The basic curriculum document that guides the field of formal education in each country often refers to how the teacher should act within the classroom lessons. At the same time, there is another element that requires reference, and that is the learner. In view of the fact that this document is general, uniform and rigid, it is not suitable for all learners. Therefore, there are many cases in which it is necessary to formulate another specific curriculum, designed for the learning style of an individual student or of a small group of students. As an example of this, in the formal education frameworks in many different countries it is possible to find a variety of educational programs with different characteristics that are built in accordance with the unique needs of students who are integrated and study in the formal education frameworks as part of the process of integration in education [2].
Keywords: language; curriculum; education; multilingual approaches; multilingual study; educational policy